Studi Kelayakan dan Kebijakan Pembiayaan dalam Pengembangan Program Pendidikan - Teguh Trianung Djoko Susanto; Any Iffatus Syarifah; Dinda Dawiyah; Faiza Adeela Kirana Budiman; Meiliani Margareta; Mitha Kurnia Yanti; Qoryafa Fatimah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
In many developing contexts (e.g., Indonesia), educational programs frequently fail due to insufficient planning and funding frameworks. Despite growing attention to feasibility analyses and educational finance individually, the combined influence of feasibility studies and financing policies on program success remains underexplored. This represents a critical research gap that our study aims to fill. To address this gap, this study conducts a systematic literature review of regulatory frameworks, financial management practices, and case studies from countries such as Japan, Singapore, and Finland. The integrated analysis reveals that comprehensive feasibility assessments — covering market demand, institutional management, financial viability, legal and technical considerations, socio-cultural alignment, and economic impact are crucial for program success. It also identifies adaptive, data-driven financing policies as essential for sustainable implementation. By synthesizing these insights, the research contributes a novel framework linking feasibility and financing considerations, providing strategic guidance for improving educational program planning. The findings imply that integrating rigorous feasibility evaluation with flexible funding mechanisms is a strategic approach to enhancing the efficiency, accountability, and competitiveness of Indonesia’s education system. For policymakers and practitioners, this means embedding coordinated evaluation and financing policies into educational program design to achieve more sustainable outcomes.